FPGA BASED DESIGN OF 1D DCT/IDCT FOR MIMO OFDM CHANNEL ESTIMATION - , Shazeeda; T.M. Shashidhar; B.G. Anupama; A.C. Chandini (European Scientific Journal, ESJ, 2014)
Orthogonal frequency division multiplexing (OFDM) is a popular digital modulation scheme for high data rate wireless transmission. A multi input multi output (MIMO) configuration is the combination of multiple antennas at the transmitter and receiver enhances the operation of OFDM. In this paper, a study of channel estimator for less complexity and good channel tracking ability for MIMO-OFDM wireless transmission is carried out. An estimator with combination of Least Square Error (LSE) estimator with Discrete Cosine Transform (DCT) is designed as the channel estimator for MIMO-OFDM system for wireless transmission. The designing is simulated and validated using ModelSim which is a functional hardware simulation, and the Verilog source code is synthesized for Vertex 5 Field Programmable Gate Array (FPGA) component. It is observed that the LSE reduces the complexity, whereas DCT increases the efficiency of the transmission.